1999
DOI: 10.1136/fn.80.2.f135
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of outcome in antenatally diagnosed renal pelvis dilatation

Abstract: Aims-To ascertain the outcome associated with antenatal renal pelvis dilatation; to recommend guidelines for postnatal investigation and determine an upper limit of normal for the anterioposterior dimensions of the fetal renal pelvis. Methods-Infants whose antenatal ultrasound scan showed a fetal renal pelvis of 5 mm or greater were investigated using postnatal renal tract ultrasound and a micturating cystogram. Isotope studies were also performed, where appropriate. Results-Vesicoureteric reflux (VUR), the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 17 publications
3
91
1
3
Order By: Relevance
“…The earliest reported fetal ultrasound was at 14 wk of gestation (21). Most studies reported that postnatal scans were not performed within 2 d after birth (17,20,22,23,(27)(28)(29)(30)(31), which may be important because newborns are initially oliguric and false-negative results are common at this time: 4 studies did not specify the earliest age at postnatal ultrasound assessment (18,29,30,33).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The earliest reported fetal ultrasound was at 14 wk of gestation (21). Most studies reported that postnatal scans were not performed within 2 d after birth (17,20,22,23,(27)(28)(29)(30)(31), which may be important because newborns are initially oliguric and false-negative results are common at this time: 4 studies did not specify the earliest age at postnatal ultrasound assessment (18,29,30,33).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those patients of more advanced gestation who were referred for prenatal urology consultation, compliance was nearly universal. An observation similar to that was made by Jaswon et al, 12 who surmised that more detailed information provided to patients by the pediatric urologist was the key to better compliance. To refer all ANH cases for prenatal urology consultation is not feasible.…”
Section: Discussionmentioning
confidence: 64%
“…16 Three small prospective studies recognized that 10 to 30% of their ANH infants were lost to follow-up. 2,12,[17][18] More recently Lee et al, 3 in a meta-analysis (using a criteria similar to ours) noted that 246 (15%) of 1678 patients with ANH were lost to follow-up. Many investigators, however, have not mentioned any loss of patients in their ANH programs.…”
Section: Discussionmentioning
confidence: 99%